(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Oil spills pose significant environmental and ecological threats to marine ecosystems. This study focuses on the development of genetically modified bacteria with enhanced capabilities for degrading petroleum hydrocarbons in oil spills. We engineered Pseudomonas putida strains to overexpress alkane hydroxylase and cytochrome P450 enzymes, key components in hydrocarbon degradation pathways. The modified strains demonstrated significantly improved degradation rates for various petroleum hydrocarbons compared to wild-type strains. In laboratory-scale experiments, the engineered bacteria showed up to 75% higher degradation efficiency for alkanes and 60% for polycyclic aromatic hydrocarbons. Field trials in simulated marine environments further confirmed the enhanced bioremediation potential of these modified strains. This research provides a promising approach for more effective and eco-friendly oil spill cleanup strategies.